ANALISIS EKSPRESI VISUAL DALAM KARYA SENI RUPA DUA DIMENSI PADA KEGIATAN EKSTRAKURIKULER DRAWING AND COLORING DI SD ISLAM BILINGUAL ANNISA KOTA SEMARANG - Rafli Fernanda; Rofian Rofian; Siti Patonah (SULUH: Jurnal Seni Desain Budaya, 2026)
Visual art is an important medium for students to express ideas, feelings, and experiences visually. This study aims to describe the implementation of the Drawing and Coloring extracurricular activity at SD Islam Bilingual Annisa Semarang City and to identify the forms and meanings of visual expression in students' two-dimensional artworks. A descriptive qualitative approach was used, with data from observation, interviews, and documentation of fifth-grade students' artworks, validated through source and technique triangulation. Verbal data were analyzed using the Miles, Huberman, and Saldana interactive model, while visual data were analyzed using Feldman's art criticism method. Results show the activity has run in a structured manner since 2014, providing students with space for free expression. Analysis of artworks themed "Special Moments of Ramadan" revealed varied lines, shapes, and colors rich in symbolic meaning, corresponding to the dawning realism stage per Viktor Lowenfeld, and diverse expression types per Herbert Read. These findings confirm that each student expresses experience through visual art in a unique way.